2024
DOI: 10.1186/s12891-024-07474-2
|View full text |Cite
|
Sign up to set email alerts
|

The learning curve of a novel seven-axis robot-assisted total hip arthroplasty system: a randomized controlled trial

Haocheng Sun,
Hanpeng Lu,
Qiang Xiao
et al.

Abstract: Bacground The aim of this study was to assess the learning curve of a novel seven-axis robot-assisted total hip arthroplasty (RaTHA) system. Methods A total of 59 patients who underwent unilateral total hip arthroplasty at our institution from June 2022 to September 2022 were prospectively included in the study. In this randomized controlled clinical trial, robot-assisted THA (RaTHA) and Conventional THA (CoTHA) were performed using cumulative sum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…Current evidence suggests that the application of traditional six-axis robotic-assist systems leads to increased accuracy in positioning the prosthesis, especially the inclination and anteversion of the acetabular cup 22 , 23 . In the present study, the RAS group demonstrated 80.85% of the inclination and anteversion within the safe zone, which was significantly higher than that in the CON group, similar to the conclusion reported by Kong et al 13 , 24 . Notably, when compared with the preoperative planning component position, the postoperative deviation was small.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Current evidence suggests that the application of traditional six-axis robotic-assist systems leads to increased accuracy in positioning the prosthesis, especially the inclination and anteversion of the acetabular cup 22 , 23 . In the present study, the RAS group demonstrated 80.85% of the inclination and anteversion within the safe zone, which was significantly higher than that in the CON group, similar to the conclusion reported by Kong et al 13 , 24 . Notably, when compared with the preoperative planning component position, the postoperative deviation was small.…”
Section: Discussionsupporting
confidence: 92%
“…People have tried to solve these problems by improving the degree of freedom of the robot. Haocheng Sun et al reported a seven-axis robot assistance system 13 . In there study the duration of operation, total blood loss, and drainage gradually decreased with the learning curve stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation